Information Cartography - Shahaf, Dafna; Guestrin, Carlos; Horvitz, Eric; Leskovec, Jure (Communications of the ACM, 2015)
"Raise your hand if you don't quite understand this whole financial crisis," said David Leonhardt's New York Times article, March 2008. The credit crisis had been going on for seven months and extensively and continuously covered by every major media outlet in the world. Despite that coverage, many readers felt they did not understand what it was about.